2017
DOI: 10.1097/mlr.0000000000000798
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Awareness of and Responses to Messages About Breast Cancer Overdiagnosis and Overtreatment

Abstract: Background Scientists, clinicians, and other experts aim to maximize the benefits of cancer screening while minimizing its harms. Chief among these harms are overdiagnosis and overtreatment. Although available data suggest that patient awareness of these harms is low, we know little about how patients respond to information about these phenomena. Objectives Using the case of breast cancer screening, this study assesses women’s awareness of and reactions to statements about overdiagnosis and overtreatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
5
21
0
Order By: Relevance
“…Our findings are consistent with prior qualitative studies and surveys which found that USPSTF's updated mammography guidelines recommending less screening had limited impact on women's screening decisions 26,27 and that women's familiarity with the concept of overdiagnosis was limited. [27][28][29] Our findings were also consistent with prior work finding that women feared underdiagnosis more than overdiagnosis, were suspicious of the underlying reasons for guideline changes, and viewed routine screening as a personal obligation. 30,31 Prior work also shows that women experienced cognitive dissonance when presented with evidence-based mammography information that conflicted with their pre-existing beliefs.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are consistent with prior qualitative studies and surveys which found that USPSTF's updated mammography guidelines recommending less screening had limited impact on women's screening decisions 26,27 and that women's familiarity with the concept of overdiagnosis was limited. [27][28][29] Our findings were also consistent with prior work finding that women feared underdiagnosis more than overdiagnosis, were suspicious of the underlying reasons for guideline changes, and viewed routine screening as a personal obligation. 30,31 Prior work also shows that women experienced cognitive dissonance when presented with evidence-based mammography information that conflicted with their pre-existing beliefs.…”
Section: Discussionsupporting
confidence: 87%
“…The ability of the ‘high flux’ ManNAc analogs to illuminate otherwise hidden metabolic features of human breast cell subtypes based on the slight chemical changes present at their N-acyl groups (e.g., ‘NAc’ vs ‘NAz’ vs ‘NAl’; Fig 1 ) raises the possibility that this class of compounds could be exploited for the detection or diagnosis of cancer. (The need for improved diagnostic approaches for breast cancer is based in part on the current over-diagnosis and over-treatment of this disease [ 87 , 88 ]). By using metabolic metrics including the capacity for sialic acid biosynthesis, which we showed can discriminate cell lines representing different stages of cancer progression using a multiple regression model, we propose that diagnostic precision can be improved if metabolic characteristics related to sialic acid biosynthesis explored in this report hold broadly across normal, earlier, and later stage cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because there were no significant differences in adjusted HRs according to age, overdiagnosis due to easy access to hospitals would increase the incidence rates and overtreatment for patients with breast, cervical, and prostate cancers simultaneously in higher-income areas. Several studies have underlined the problems of overdiagnosis and overtreatment (Nagler et al, 2017;Morgan et al, 2017;Jegerlehner et al, 2017). The Norwegian Breast Cancer Screening Program was conducted in 1995 and 1996 (Falk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%